Agentes socioambientais urbanos e a ativação da cidadania: uma proposta de avaliação do programa carta da terra em ação - Marcondes, Débora Pontalti (2021)
The Earth Charter in Action Program (Carta) was conceived by the City Hall of São Paulo to encourage citizens to develop critical evaluation of urban socio-environmental situations in their territories. In its eleven years of history (2009 - 2019), more than 600 postmen were trained and, in turn, developed socio-environmental actions in their territories, aiming to transform São Paulo into a more just and sustainable city. This research was developed in a theoretical framework that recognizes the complexity of the territory and the importance of activating citizenship, as well as recognizing the need for critical and systematic analysis of environmental education programs. The case study aims to evaluate the referred program in promoting the activation of citizenship. To this end, it undertakes to systematize the process of creating the Carta and the changes that occurred throughout the history of the program, as well as to classify the socio-environmental actions developed by the postmen, according to the typology of Ekman & Amnå (2012). It should be noted that the changes that occurred over the sixteen classes (2009 - 2019) ensured that the program was kept alive and in line with the demands of citizens, reflecting on socio-environmental actions that were transformed over the period studied, making the activation of citizenship more complex for the citizens who participated in the program.